2021
DOI: 10.1371/journal.pone.0252795
|View full text |Cite
|
Sign up to set email alerts
|

Visual preference for social vs. non-social images in young children with autism spectrum disorders. An eye tracking study

Abstract: Autism Spectrum Disorders (ASD) are associated to social attention (SA) impairments. A gaze bias to non-social objects over faces has been proposed as an early marker of ASD. This bias may be related to the concomitant circumscribed interests (CI), which question the role of competing objects in this atypical visual behavior. The aim of this study was to compare visual attention patterns to social and non-social images in young children with ASD and matched typical controls (N = 36; age range 41–73 months) ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 64 publications
2
17
0
1
Order By: Relevance
“…One study [47] showed that children with ASD did not attend less to faces than their TD peers when they were presented with happy faces. Taken together, these results imply that differences in attention to face in children with ASD in comparison to their TD peers are subtle and context dependent [48].…”
Section: Discussionmentioning
confidence: 75%
“…One study [47] showed that children with ASD did not attend less to faces than their TD peers when they were presented with happy faces. Taken together, these results imply that differences in attention to face in children with ASD in comparison to their TD peers are subtle and context dependent [48].…”
Section: Discussionmentioning
confidence: 75%
“…Concerning the exploration of facial features, children with ASD in both groups gazed faster and explored the mouth and nose areas longer, while they gazed slower and explored the outside area less compared to all other facial features. Previous researches on children with ASD have reported a deficit in the exploration of faces compared to the rest of the visual scene ( Klin et al, 2003 ; Riby and Hancock, 2008 ; Vacas et al, 2021 ). Results from the present study do not necessarily contradict those findings, because the outside area was blank and did not contain items (e.g., objects, furniture, and decor) that may potentially attract children’s attention.…”
Section: Discussionmentioning
confidence: 96%
“…A reduced attention to faces in individuals with ASD is often reported, along with a stronger exploration of other items from the visual scene (e.g., objects, bodies, etc.) ( Klin et al, 2002 , 2003 ; Riby and Hancock, 2008 ; Howard et al, 2019 ; Vacas et al, 2021 ). Alterations of visual exploration strategies of faces in individuals with ASD are also observed.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have hypothesized that autism is characterized by domain-specific altered responsiveness to social rewards ( Chevallier et al, 2012 ; Kohls et al, 2012 ), while others have proposed domain-general differences in autism that are observed across reward stimuli types ( Bottini, 2018 ). While it has been reported that young autistic children show altered attentional priority (which could indicate altered motivation) for interest images and social images ( Sasson et al, 2008 ; Vacas et al, 2021 ), relatively little work has investigated affective responses to rewarding stimuli in young children. Assessing whether affective reward responsiveness varies by reward type in young children with autism, and if differences relate to intense interests, is a valuable area of future study.…”
Section: Discussionmentioning
confidence: 99%